Gamma irradiation results of total phenolic content and antioxidant capacity of ethanol extract of white tea (Camellia sinensis) - bina lohita sari (Research Institute for Tea and Cinchona, 2017)
White tea is produced from tea shoots with simplest processing. This unfermented tea contents a lot of chemical constituents such as polyphenol that present potent antioxidant capacity. In this research, we analyzed total phenolic content and antioxidant capacity of white tea ethanol extract after exposing simplicial with gamma rays doses of 0; 2.5; 5.0; 7.5; 10.0; and 12.5 kGy. Gamma ray irradiation in pharmaceutical can be used as one of the most efficient method to reduce microorganisms. The extraction of simplicia used Microwave-assisted extraction (MAE) with ethanol 60% as the extraction solvent. The determination result of total phenolic levels of white tea extract irradiated at a doses ofÂ 0; 2.5; 5.0; 7.5; 10.0; and 12.5 kGy were 121.62; 148.73; 187.28; 161.88; and 162.28 mg GAE/g. The antioxidant capacity value was 16.67; 19.63; 30.08; 25.60; 23.11; 16.15 %. The total phenolic content and antioxidant capacity showed the highest irradiation at 5 kGy dose.